2013
DOI: 10.1111/nyas.12314
|View full text |Cite
|
Sign up to set email alerts
|

Issues in the timing of integrated early interventions: contributions from nutrition, neuroscience, and psychological research

Abstract: A central issue when designing multi-dimensional biological and psychosocial interventions for children who are exposed to multiple developmental risks is identification of the age period(s) in which such interventions will have the strongest and longest lasting impact (sensitive periods). In this paper we review nutritional, neuroscience and psychological evidence on this issue. Nutritional evidence is used to identify nutrient sensitive periods of age-linked dimensions of brain development, with specific ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
105
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(124 citation statements)
references
References 174 publications
5
105
0
5
Order By: Relevance
“…Our findings suggest that, beyond these potentially synergistic risk factors, there remains a significant direct impact of early adverse caregiving at the cellular level in primates (Hackman, Farah, & Meaney, 2010; Shonkoff, Garner, & Committee on Psychosocial Aspects of Child and Family Health, 2011). These findings indicate that the first months of life in macaques, similar to the first years in humans, are a very vulnerable developmental window when disruption in caregiving, however brief, can result in persistent changes with long-term physiological implications (Humphreys et al, in press; Nelson, Fox, & Zeanah, in press; Wachs, Georgieff, Cusick, & McEwen, 2014). …”
Section: Discussionmentioning
confidence: 97%
“…Our findings suggest that, beyond these potentially synergistic risk factors, there remains a significant direct impact of early adverse caregiving at the cellular level in primates (Hackman, Farah, & Meaney, 2010; Shonkoff, Garner, & Committee on Psychosocial Aspects of Child and Family Health, 2011). These findings indicate that the first months of life in macaques, similar to the first years in humans, are a very vulnerable developmental window when disruption in caregiving, however brief, can result in persistent changes with long-term physiological implications (Humphreys et al, in press; Nelson, Fox, & Zeanah, in press; Wachs, Georgieff, Cusick, & McEwen, 2014). …”
Section: Discussionmentioning
confidence: 97%
“…In this same study, supplements between ages 12–36 months did not provide additional benefits [47]. As a result, the timing of supplementation is critical, and it appears that earlier (even during the prenatal period) is better for the developing brain [48–49]. Another supplementation study during pregnancy found that iron deficient mothers who began iron supplementation before 20 weeks gestation had infants with higher birth weights, a smaller likelihood of low birth weight (LBW) infants, and fewer preterm LBW infants compared to women who started supplementation if iron deficient at 28 or 38 weeks [50].…”
Section: Prenatal Intervention Studiesmentioning
confidence: 99%
“…However, longitudinal research is required to determine the impact of differential cortisol and IL-6 concentrations on children's future ability to maintain hormonal and immune system balance and to prevent neurobiological changes (Dhabhar 2009;Kapur et al 2012). Of importance is the possibility that if applicable treatments are started early, during a prodromal stage, there may be a more beneficial outcome for a child or adolescent who has been subjected to severe early life stress (Wachs et al 2014). Finally, while at the time of this study young girls were the predominant patient group, there is a need to investigate the biological impact of sexual abuse in young boys.…”
Section: Discussionmentioning
confidence: 97%